A Duration Analysis of CONALEP (Mexico's National Technical Professional School) - López-Acevedo, Gladys (World Bank, Washington, D.C., 2013)
Mexico's National Technical Professional School (Colegio Nacional de Educación Profesional Técnica, CONALEP) is the largest technical education system in the country. CONALEP serves low-income students at the upper-secondary school level in Mexico. Using graduate tracer surveys from CONALEP, the author analyzes the impact of modular courses and reform programs implemented by CONALEP in 1991-92 on CONALEP graduates' labor market outcomes. Results indicate that graduates from the pre-reform program had to search longer for a job compared with those of the post-reform program. Graduates from the post-reform program have 45 percent higher probability of finding a job than those from the pre-reform program. However, the pre-reform program cohorts earned higher hourly wages than those from the post-reform program.